SOI based nanowire single-electron transistors: design, simulation and process development - Uda Hashim; A. Rasmi; Samsudi Sakrani (Universiti Malaysia Perlis, 2008)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1; issue 1, 2008.